CONTROL SYSTEM HYDROPONIC PLANTS WEB BASED USING RASPBERRY PI AS SERVER - Putra, Afrian Anggara; Rasmana, Susijanto Tri; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2017)
Abstract: Hydroponics is a method of farming without the use of soil as a medium capable of providing satisfactory results and efficient production.And with the rapid advancement of technology comes concept of IOT (Internet Of Things) that generates interactions between the objects with other objects that will be connected automatically without distance and time. The final task is to introduce how to control hydroponics using concept of IOT (Internet Of Things). This electronic equipment using microcontroller arduino as a circuit which is connected to the hydroponic plants and raspberry pi as a server using the method of nutrient control and monitoring via the web. The system designed has been able to reduce the waste of time. There has also been able to do and mixing nutrients through the user input using the web. So that the tool is able to improve the efficiency and effectiveness of the use of nutrients daily. Based on these test results in a success rate of almost 100%.Keyword: Hydroponics, Arduino, Raspberry Pi, and Web Server.